Caribbean Report 04-06-1990 - Crosskill, Hugh (anchor); Vaz, Douglas (interviewee); Nunez, Philip (interviewee) (The British Broadcasting Corporation, 1990)
Carla Hills, US Trade Ambassador, comments on the attempts by the European courtiers to bribe the markets instead of allowing the entrepreneurs to succeed base on price and quality. Secondly, the opposition Jamaica Labour Party holds its annual conference this weekend with at least five members calling on party leader, Edward Seaga, to improve the lines of communication within the party. This so-called “Gang of Five” has been accused of trying to unseat Edward Seaga and announces that they will not be seeking executive posts in the upcoming conference. The report concludes with the call by a member of the Caricom Committee on Transportation for a firm commitment to the establishment of a multi-national carrier to serve the Caribbean. Philip Nunez comments on the structure of the proposed Caribbean airlines.
1. Interview with Carla Hills, US Trade Representative (00:00-00:53)
2. Jamaica Labour Party holds its annual conference with at least five members calling on party leader, Edward Seaga, to improve the lines of communication within the party. Hugh Crosskill interviews Douglas Vaz, a former Trade and Industry Minister (00:54-06:00)
3. Caricom needs to make a firm commitment to the establishment of a multi-national air carrier to serve the Caribbean. Interview with Philip Nunez, an advisor on transportation to the Trinidad and Tobago government (06:01-08:41)
Report commences in the middle of a segment.
Keywords: Trade -- Caribbean Area; Jamaica Labour Party -- Congresses; Jamaica -- Politics and government; Seaga, Edward P. G.; Airlines -- Caribbean Area; Transportation -- Caribbean Area; Gang of Five -- Jamaica